FACTORS AFFECTING EMPLOYEE JOB SATISFACTION IN UNIVERSITIES IN SOMALIA - AHMED, HILOWLE ABDULLAHI; GICHINGA, Dr LUCY (IJRDO - Journal of Business Management, 2016)
the main purpose of this study was to investigate the factors affecting employee job satisfaction in universities in Mogadishu-Somalia with a specific reference to Mogadishu Universities-Somalia. This study was guided by the following three research questions: What is the influence of organizational culture on employee job satisfaction in universities in Mogadishu- Somalia? What is the influence of work environment on employee job satisfaction in universities in Mogadishu- Somalia? How does the leadership style influence employee job satisfaction in universities in Mogadishu-Somalia? A descriptive research design was being adopted. The dependent variable was employee job satisfaction while the independent variables were organizational culture, work environment and leadership style factors of employee job satisfaction. Proportionate stratified random sampling technique was used . The results reveal that organizational culture , work environment and leadership style have significant and positive effects on employee job satisfaction, while organizational culture have insignificant effects on employee job satisfaction in the universities in Mogadishu Somalia.